Single-visit apexification in immature necrotic teeth using mineral trioxide aggregate as an apical plug: Case series - Nidhi Singh; Neelam Mittal; Harakh Chand Baranwal; Richik Tripathi; Chi Koy Wang (Wolters Kluwer Medknow Publications, 2019)
Apexification is a procedure for closure of the open apex in an immature necrotic tooth. Apexification with calcium hydroxide is considered as the gold standard. However, this technique is associated with certain difficulties such as very long treatment period, possibility of tooth fracture, and incomplete calcification of the bridge. Single-visit mineral trioxide aggregate (MTA) apexification has become popular over the calcium hydroxide technique. In this article, three case reports of 3 months to 1-year follow-up are presented, which were treated by the single visit apexification procedure which includes recent artificial barrier methods with MTA as the apical plug and the rest of the canal was obturated with thermoplastisized gutta-percha.